2011
DOI: 10.1371/journal.pone.0028039
|View full text |Cite
|
Sign up to set email alerts
|

Role of β-Catenin in Post-Meiotic Male Germ Cell Differentiation

Abstract: Though roles of β-catenin signaling during testis development have been well established, relatively little is known about its role in postnatal testicular physiology. Even less is known about its role in post-meiotic germ cell development and differentiation. Here, we report that β-catenin is highly expressed in post-meiotic germ cells and plays an important role during spermiogenesis in mice. Spermatid-specific deletion of β-catenin resulted in significantly reduced sperm count, increased germ cell apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 80 publications
1
33
0
Order By: Relevance
“…In other studies, germ cell-specific β-catenin CKO mediated by Stra8-iCre, which is expressed in differentiating spermatogonia at the onset of differentiation, did not cause a detectable phenotype (49). In addition, spermatid-specific β-catenin CKO mediated by Prm1-Cre has been shown to cause impaired fertility as a result of reduced sperm counts (50). Another group reported disrupted spermatogenesis in both loss-and gain-of-Wnt signaling function experiments using AhCre (37).…”
Section: Discussionmentioning
confidence: 91%
“…In other studies, germ cell-specific β-catenin CKO mediated by Stra8-iCre, which is expressed in differentiating spermatogonia at the onset of differentiation, did not cause a detectable phenotype (49). In addition, spermatid-specific β-catenin CKO mediated by Prm1-Cre has been shown to cause impaired fertility as a result of reduced sperm counts (50). Another group reported disrupted spermatogenesis in both loss-and gain-of-Wnt signaling function experiments using AhCre (37).…”
Section: Discussionmentioning
confidence: 91%
“…20,21 The removal of β-catenin in the mouse spermatid increases apoptosis, acrosome defects, abnormal chromatin condensation, and degradation of Sertoli-germ cell junctions in which can lead to infertility. 22 Overexpression of β-catenin leads to uncontrolled proliferation, inhibition of differentiation in Sertoli cells and their function to support germ cells in mice. 23 As a result, relationship of Wnt/β-catenin signaling dysfunction in sertoli, germ cell, and infertility has been confirmed.…”
mentioning
confidence: 99%
“…On the other hand, Kerr et al (2014) have recently detected nuclear b-catenin in murine spermatocytes and spermatids and based on mouse model with b-catenin mutation (AhCre Ctnnb1 fl/fl ) proposed Wnt/b-catenin signaling as required at several stages of spermatogenesis. It should be added that other authors also reported that deletion of b-catenin gene or its stabilizing mutation in germ cells caused germ cell deficiency and spermatogenic failure (Kimura et al, 2006;Chang et al, 2011). In contrast, very recently Rivas et al (2014) have showed that conditional deletion of b-catenin in germ cells had no effect on germ cell.…”
Section: (A) (B)mentioning
confidence: 99%
“…They form complexes between Sertoli cells at the BTB and between Sertoli cells and elongated spermatids (Vogl et al, 2000). Cadherin-catenin complexes do not only provide mechanical adhesion in the seminiferous epithelium; they also play a crucial role in germ cell morphogenesis and differentiation (Rowlands et al, 2000;Honecker et al, 2004;Chang et al, 2011). In particular, the b-catenin is involved in germ cell maturation by regulating interactions and signaling at the Sertoli cellgerm cell interface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation